Identification of cancer associated molecular changes in histologically benign vulval disease found in association with vulval squamous cell carcinoma using Fourier transform infrared spectroscopy. Issue 48 (23rd November 2016) - Frost, Jonathan; Ludeman, Linmarie; Hillaby, Kathryn; Gornall, Robert; Lloyd, Gavin; Kendall, Catherine; Shore, Angela C.; Stone, Nick
Abstract : Evaluation of infrared spectroscopy for assessing the biomolecular changes which occur in the vulva leading to the development of cancer. Abstract : This study evaluates the capability of Fourier transform infrared spectroscopy (FTIR-S) in the differentiation of molecular changes in vulval intraepithelial neoplasia (VIN) and lichen sclerosus (LS) found in association with vulval squamous cell carcinoma (SCC), compared with VIN and LS found in isolation. 48 sections of vulval epithelium with features of VIN ( n = 24) or LS ( n = 24) underwent FTIR-S micro-spectroscopic mapping. Spectra from each section were correlated with the pathological diagnoses and the presence of concurrent SCC. Spectral variance was explored using principal component analysis and a multivariate linear discriminant classification model was developed and validated with leave one sample out cross validation. The discriminant model was able to correctly identify FTIR-S spectra taken from samples of VIN and LS found in association with SCC from those found in isolation with a sensitivity of 82% and specificity of 93% for LS and sensitivity of 75% and specificity of 94% for VIN. The discriminant model was adjusted to maximise sensitivity whilst conceding specificity on a per patient basis and could differentiate LS associated with SCC with a sensitivity of 100% and specificity of 84% and VIN associated with SCC sensitivity of 100% and specificity 58%. In distinguishing VIN and LS found in association with SCC from that found in isolation FTIR-S offers a potential technique for the assessment of molecular changes in the vulva that predispose to the development of SCC. Further study is needed to assess the ability of FTIR-S to risk stratify patients with VIN or LS.